2010
DOI: 10.1186/1758-2652-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the hotspots: investigating spatial and demographic variations in HIV infection in small communities in South Africa

Abstract: BackgroundIn South Africa, the severity of the HIV/AIDS epidemic varies according to geographical location; hence, localized monitoring of the epidemic would enable more effective prevention strategies. Our objectives were to assess the core areas of HIV infection in KwaZulu-Natal, South Africa, using epidemiological data among sexually active women from localized communities.MethodsA total of 5753 women from urban, peri-rural and rural communities in KwaZulu-Natal were screened from 2002 to 2005. Each partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 15 publications
2
70
1
4
Order By: Relevance
“…In terms of STD cases, our study found that there was no spatial cluster for STDs, which seemed to be contradictory to studies done in Africa 28 and China 29 previously. This study was designed to obtain a population-representative sample in Guangzhou.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of STD cases, our study found that there was no spatial cluster for STDs, which seemed to be contradictory to studies done in Africa 28 and China 29 previously. This study was designed to obtain a population-representative sample in Guangzhou.…”
Section: Discussioncontrasting
confidence: 99%
“…Mathematical models based on empirical data provide indirect support for targeted TB elimination strategies. Data from Rio de Janeiro suggest that, as with other diseases 8,31,76,77 , targeting hotspots containing 6% of the population on a district level (identified from local notification rates) could reduce city-wide TB incidence to a similar degree as an intervention of equal intensity covering the remaining 94% of the population 78 .…”
Section: Empirical Evidence For Local Approaches To End Tbmentioning
confidence: 99%
“…A variety of approaches have proven successful in understanding where infections are occurring. Geospatial and geovisualization approaches have included cluster analyses to define the relationship between HIV and community-level factors [6, 7], descriptions of the spatial distribution of high risk behaviors and high HIV infection rates [710], and identification of areas for tuberculosis, syphilis and HIV screening [11]. …”
Section: Introductionmentioning
confidence: 99%